Dispersion of natural molybdenum disulfide (MoS2) nanosheets for the electrocatalytic hydrogen evolution reaction (HER) - Arcangel, Michaela R.; Mercado, Candy C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Alkaline electrolysis has been considered in commercial applications as a clean and efficient technology for the growing demand for hydrogen fuel in fuel cell technologies. To speed up the Hydrogen Evolution Reaction (HER), several materials including precious metals with appropriate surface properties have been considered as catalyst. Difficulty in common synthesis of catalysts through chemical means with variations in morphology and higher economics brings the need for a more scalable and cost-effective approach. Natural molybdenum disulfide (MoS2) in the form of the crystalline Molybdenite has been extracted from mine waste tailings (Residue Impoundment Sludge) in FCF Minerals Corp, Nueva Viscaya, Philippines through Rougher-Cleaner route of Oil-Agglomeration Froth Flotation with 99.97% final recovery and final grade of 74.80% Mo from a low grade Mo source (1.0S2% Mo) with ultrafine particles with interference of organic matter and silicates, with SEM/EDX photomicrographs of probable fine and flaky molybdenite particles on a silicate matrix. MoS2 nanosheets were produced from exfoliation of Rougher (1st stage flotation) and Cleaner 2 (final stage flotation) concentrates in OAF flotation through high-shear milling in common household surfactant solution and the dispersion in varying concentrations of Ethanol (EtOH). Agglomeration due to the retained oil from OAF has no significant effect on particle size distribution of PBM products (Head sample, Rougher concentrate, Cleaner 1 concentrate and Cleaner 2 concentrate) with average Cumulant diameters of 26.27±66.S6 nm, 25.69±50.40 nm, 25.93±67.58 nm and 25.51±61.23 nm, respectively. Exfoliated and dispersed Rougher (50%EtOH) and Cleaner 2 (20%, 50% and 80% EtOH) products were drop-casted onto a conductive substrate (0.025 cm2 NiO films) to serve as a cathode of in an electrolytic cell with 1 M KOH as electrolyte, Pt counter electrode and sat'd Ag/AgCI as reference electrode. Voltage bias of 0.5V at 0.1 V/s at a range of -0.7 to 0.3V was applied to derive the Linear Sweep Voltammograms of each cathode at 4 trials. There was a significant difference between Rougher and Cleaner 2 (50%EtOH) cathodes with the former having a wider range of performance and instability with the progression of trials that may be due to the lower grade of Mo on the sample and unwanted reactions on the cathode surface. There was a significant difference in Cleaner 2 cathodes in varying EtOH concentrations. Best electrocatalytic performance among the three was found at 50%EtOH with the lowest average onset potential of -0.341V, while 20% and 80% EtOH having -0.354 and -0.352V, respectively. The higher onset potentials were due to the summative of either ineffective dispersion or lower MoS2 concentration. Results show that the dispersed MoS2 from OAF flotation of fine molybdenite from mine waste tailings is a viable source of HER electrocatal yst in alkaline medi
Submitted in partial fulfillment of the requirements of Metallurgical Engineering 199.
Thesis (Bachelor of Science in Metallurgical Engineering)--University of the Philippines Diliman
Keywords: Molybdenum disulfi